Comparison of Early and Mid-Term Outcomes After Fenestrated-Branched Endovascular Aortic Repair in Patients With or Without Prior Infrarenal Repair. (August 2022) - D'Oria, Mario; Budtz-Lilly, Jacob; Lindstrom, David; Lundberg, Goran; Jonsson, Magnus; Wanhainen, Anders; Mani, Kevin; Unosson, Jon
Objective: The purpose of this study was to compare short- and mid-term outcomes of fenestrated-branched endovascular repair (F-BEVAR) of pararenal (PRAA)/thoracoabdominal (TAAA) aortic aneurysms in patients with or without prior endovascular/open (EVAR/OAR) infrarenal aortic repair. Methods: Data from consecutive F-BEVAR (2010–2019) at two high-volume aortic centers were retrospectively reviewed. Primary endpoints were technical success, 30-day mortality, and overall survival. Secondary endpoints included 30-day major adverse events (MAE), freedom from type I/III endoleaks, reinterventions, sac expansion, and target vessel (TV) primary patency. Results: A total of 222 consecutive patients were included for analysis; of these 58 (26.1%) had prior infrarenal repair (EVAR=33, OAR=25) and 164 (73.9%) had native PRAA/TAAA. At baseline, patients with prior infrarenal repair were older (mean age=75.1 vs 71.6 years, p=.005) and the proportion of females was lower (8.6% vs 29.3%, p=.002). Technical success was 97.8% (n=217) in the entire cohort, without any significant differences between study groups (94.8% vs 98.8%, p=.08). At 30 days, there were no significant differences between patients with prior infrarenal repair as compared with those without in rate of MAE (44.8% vs 54.9%, p=.59). The 5-year estimate of survival for those who underwent native aortic repair was 61.6%, versus 61.3% for those who had a previous repair (p=.67). The 5-year freedom from endoleaks I/III estimates were significantly lower in patients who had prior infrarenal repair as compared with patients undergoing treatment of native aneurysms (57.1% vs 66.1%, p=.03), mainly owing to TV-related endoleaks (ie, type IC and/or IIIC endoleaks). No significant differences were found between study groups in rates of reinterventions and TV primary patency. Five-year estimates of freedom from sac increase >5mm were significantly lower in patients who received F-BEVAR after previous infrarenal repair as compared with those who underwent treatment of native aneurysms (48.6% vs 77.5%, p=.002). Conclusions: F-BEVAR is equally safe and feasible for treatment of patients with prior infrarenal repair as compared with those undergoing treatment for native aneurysms. Increased rates of TV-related endoleaks were observed which could lead to lower freedom from aneurysm sac shrinkage during follow-up. Nevertheless, the 5-year rates of reinterventions and TV patency were similar, thereby indicating that overall effectiveness of treatment remained satisfactory at mid-term.